Route-following assistance for travelers with cognitive impairments: A comparison of four prompt modes - Fickas, Stephen; Sohlberg, McKay; Hung, Pei-Fang (International journal of human-computer studies, 2008)
Navigational skills, which are fundamental to community travel and hence, personal independence, are often disrupted in people with cognitive impairments. Assistive technology, in the form of navigation devices, are being developed that can support community navigation by delivering directional information. Selecting an effective mode to provide route-prompts is a critical design issue. This study evaluated the differential effects on pedestrian route following using different modes of prompting delivered via an electronic device for travelers with severe cognitive impairments. The research design used was a within subject comparison to evaluate potential differences in route-following performance when travelers received directions using four different prompt modes: (1) aerial map image, (2) point of view map image, (3) audio direction/no image and (4) text-based instructions/no image. Twenty travelers with severe cognitive impairments due to acquired brain injury walked four equivalent routes using four different prompting modes delivered via a wrist-worn navigation device. Navigation scores were computed that captured accuracy and confidence during navigation. Results of the repeated measures analysis of variance suggested that participants performed best when given prompts via speech-based audio directions. The majority of the participants also preferred this prompting mode. Findings are interpreted in the context of cognitive resource allocation theory.